EDUKASI MASYARAKAT TENTANG PENTINGNYA PERAN SERTA DALAM PEMELIHARAAN SISTEM SALURAN DRAINASE DI DESA RANDUSANGA KULON KECAMATAN BREBES KABUPATEN BREBES - Atiyah Barkah (Universitas Wijayakusuma Purwokerto, 2026)
Drainage is the natural or artificial removal of water from the surface or subsurface of a location. Drainage is a system for channeling rainwater. According to Minister of Public Works Regulation No. 12 of 2014 concerning the Implementation of Rural/Urban Drainage Systems, drainage is a water channel located on the surface or underground, formed naturally or artificially. Drainage systems function to drain standing water, control excessive accumulation of rainwater runoff, control erosion, road damage, and infrastructure damage, and manage water quality. Drainage systems play a crucial role in creating a healthy environment, especially in densely populated areas. Ongoing evaluation and mentoring are essential for behavioral change and the sustainability of drainage maintenance efforts in villages. By actively involving the community and providing necessary support, drainage channel maintenance can be more effective and sustainable